The Cause of Hereditary Hearing Loss in GJB2 Heterozygotes-A Comprehensive Study of the GJB2/DFNB1 Region - Safka Brozkova, Dana; Uhrova Meszarosova, Anna; Lassuthova, Petra; Varga, Lukáš; Staněk, David; Borecká, Silvia; Laštůvková, Jana; Čejnová, Vlasta; Rašková, Dagmar; Lhota, Filip; Gašperíková, Daniela; Seeman, Pavel (Genes, 2021)
Hearing loss is a genetically heterogeneous sensory defect, and the frequent causes are biallelic pathogenic variants in the GJB2 gene. However, patients carrying only one heterozygous pathogenic (monoallelic) GJB2 variant represent a long-lasting diagnostic problem. Interestingly, previous results showed that individuals with a heterozygous pathogenic GJB2 variant are two times more prevalent among those with hearing loss compared to normal-hearing individuals. This excess among patients led us to hypothesize that there could be another pathogenic variant in the GJB2 region/DFNB1 locus. A hitherto undiscovered variant could, in part, explain the cause of hearing loss in patients and would mean reclassifying them as patients with GJB2 biallelic pathogenic variants. In order to detect an unknown causal variant, we examined 28 patients using NGS with probes that continuously cover the 0.4 Mb in the DFNB1 region. An additional 49 patients were examined by WES to uncover only carriers. We did not reveal a second pathogenic variant in the DFNB1 region. However, in 19% of the WES-examined patients, the cause of hearing loss was found to be in genes other than the GJB2. We present evidence to show that a substantial number of patients are carriers of the GJB2 pathogenic variant, albeit only by chance.
Keywords: percepční nedoslýchavost; Humans; lidé; frekvence genu; Connexin 26; Mutation; Heterozygote; Gene Frequency; konexin 26; Hearing Loss, Sensorineural; heterozygot; mutace